Sexual Psychoeducation of Pre-School Children: Teachers' Strategies and Barriers in Teaching Self-Protection - Rakhmawati, Ellya; Yuliejatiningsih, Yovitha; Rakhmawati, Dini (Kuras Institute, 2024)
There is an urgency to provide sexual psychoeducation to young children because of the high number of cases of violence against children and women in the city of Semarang. This fact is supported because there are still many teachers who consider sex education to be taboo. This research uses a qualitative method with a phenomenological approach. This research included 15 kindergarten teachers taken from two kindergarten schools in Semarang City. Data collection through observation and in-depth interviews. Document analysis through photos, videos, and audio recordings from teacher participants. This research aims to explore teachers' strategies and barriers in teaching self-protection in sexual psychoeducation programs for pre-school children. This research reveals teachers' strategies in teaching children sexual psychoeducation regarding self-protection, namely, teachers use learning media, create special classes, apply habituation, and create safe and comfortable classes. Barriers for teachers in providing sexual psychoeducation to children are the limited age of children, sexual education being a taboo subject, limited school facilities and the number of teachers, as well as different levels of understanding and characteristics of children.